2020
DOI: 10.1111/1744-7917.12882
|View full text |Cite
|
Sign up to set email alerts
|

A dsRNA‐degrading nuclease (dsRNase2) limits RNAi efficiency in the Asian corn borer (Ostrinia furnacalis)

Abstract: The efficiency of RNA interference (RNAi) varies substantially among different insect species. Rapid degradation of double‐stranded RNA (dsRNA) by dsRNA‐degrading nucleases (dsRNases) has been implicated to cause low RNAi efficiency in several insect species. In this study, we identified four dsRNase genes (OfdsRNase1, OfdsRNase2, OfdsRNase3 and OfdsRNase4) from the Asian corn borer (Ostrinia furnacalis) transcriptome database. Bioinformatic analyses showed that each deduced protein sequence contained endonucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 51 publications
1
33
0
7
Order By: Relevance
“…To improve the knockdown efficiency, dsRNA of dsRNase gene is sequentially‐ or co‐fed with a target RNAi gene as a way of enhancing dsRNA stability in insect (Chung et al, 2018; Fan et al, 2020; Garcia et al, 2017; Luo et al, 2017; Peng, Wang, Chen, et al, 2020; Prentice et al, 2019; Song et al, 2017; Spit et al, 2017; Tayler et al, 2019; Yoon et al, 2020). Moreover, the encapsulation of naked dsRNA has been used for improving dsRNA delivery and protecting dsRNA degradation from dsRNases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To improve the knockdown efficiency, dsRNA of dsRNase gene is sequentially‐ or co‐fed with a target RNAi gene as a way of enhancing dsRNA stability in insect (Chung et al, 2018; Fan et al, 2020; Garcia et al, 2017; Luo et al, 2017; Peng, Wang, Chen, et al, 2020; Prentice et al, 2019; Song et al, 2017; Spit et al, 2017; Tayler et al, 2019; Yoon et al, 2020). Moreover, the encapsulation of naked dsRNA has been used for improving dsRNA delivery and protecting dsRNA degradation from dsRNases.…”
Section: Discussionmentioning
confidence: 99%
“…RNAi is successful in some coleopteran insects, whereas it is relatively ineffective in other orders (Miller et al, 2012; Terenius et al, 2011; Zhu et al, 2011). The major reason is the presence of dsRNases in saliva, gut, or hemolymph that induces the degradation of introduced dsRNAs (Allen & Walker, 2012; Arimatsu et al, 2007; Cooper et al, 2020; Fan et al, 2020; Garcia et al, 2017; Luo et al, 2017; Peng, Wang, Zhu, et al, 2020; Prentice et al, 2019; Shukla et al, 2016; Song et al, 2017; Spit et al, 2017; Wang et al, 2016; Wynant et al, 2014). Another reason is the entrapment of dsRNAs in endosomes after endocytosis, resulting in an inefficient RNAi response, as shown in a lepidopteran cell line (Yoon et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo co-targeting of dsRNases together with other vital genes has been demonstrated to significantly reduce gene expression and insect performance, compared to targeting only the vital gene, in insects of the orders Coleoptera (Almeida Garcia et al, 2017;Spit et al, 2017;Prentice et al, 2019;Peng et al, 2020a), Hemiptera (Luo et al, 2017;Chung et al, 2018;Kaur et al, 2020;Sharma et al, 2021), and Diptera (Tayler et al, 2019;Giesbrecht et al, 2020). Additional studies also suggest that inadequate oral RNAi is due to the presence of dsRNases in an even greater diversity of insect taxa (Song et al, 2017;Ghodke et al, 2019;Cooper et al, 2020;Fan et al, 2020;Peng et al, 2020b;Yoon et al, 2021).…”
Section: Targeting Dsrnasesmentioning
confidence: 99%
“…Recent studies have demonstrated that degradation of dsRNA by dsRNAdegrading nucleases (dsRNase) may occur prior to cellular uptake. Extracellular degradation of dsRNA, notably in the gut, may explain the low efficiency of oral RNAi (Garbutt et al, 2013;Singh et al, 2017;Peng et al, 2018;Prentice et al, 2019;Cooper et al, 2020;Fan et al, 2020;Chen et al, 2021;Yoon et al, 2021). The first insect dsRNase identified in the midgut fluid of the domestic silk moth (Bombyx mori), contains a signal peptide and a non-specific endonuclease domain (Arimatsu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%